2017
DOI: 10.1007/s40620-017-0395-9
|View full text |Cite
|
Sign up to set email alerts
|

Defective glycolysis and the use of 2-deoxy-d-glucose in polycystic kidney disease: from animal models to humans

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is an inherited renal disease characterized by bilateral renal cyst formation. ADPKD is one of the most common rare disorders, accounting for ~10% of all patients with end-stage renal disease (ESRD). ADPKD is a chronic disorder in which the gradual expansion of cysts that form in a minority of nephrons eventually causes loss of renal function due to the compression and degeneration of the surrounding normal parenchyma. Numerous deranged pathways have been id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…Altered renal energy metabolism is a common characteristic of many forms of kidney disease [14]. In particular, changes in expression and activity of glycolytic enzymes have been demonstrated in several kidney diseases including polycystic kidney disease, ischaemic acute kidney injury and diabetic nephropathy [2, 46]. Pre-eclampsia is a systemic hypertensive disorder of pregnancy, which is a major cause of maternal and perinatal morbidity and mortality [7].…”
Section: Introductionmentioning
confidence: 99%
“…Altered renal energy metabolism is a common characteristic of many forms of kidney disease [14]. In particular, changes in expression and activity of glycolytic enzymes have been demonstrated in several kidney diseases including polycystic kidney disease, ischaemic acute kidney injury and diabetic nephropathy [2, 46]. Pre-eclampsia is a systemic hypertensive disorder of pregnancy, which is a major cause of maternal and perinatal morbidity and mortality [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cystic growth in PC1-deficient kidneys is fueled by a Warburg-like metabolic switch characterized by increased anaerobic glycolysis at the expense of oxidative phosphorylation [ 7 ]. How PKD1 attenuates glycolysis is unknown [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that PC1 lacking cells consume high levels of glucose, preferentially using it in aerobic glycolysis for their energy production (Rowe et al, 2013 ). Indeed, mitochondrial abnormality exists from an early phase of ADPKD, underlining a relationship between mitochondria and renal polycystic diseases (Li et al, 2012 ; Rowe et al, 2013 ; Magistroni and Boletta, 2017 ; Padovano et al, 2017 ). In line, an association between mitochondria abnormalities and cystogenesis has been reported in cyst-lining cells in ADPKD model mice and in rats (Ishimoto et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%